Cost of Quality Models in Continuous Production Systems with Deteriorating Quality: A Review and Research Agenda - Irna Ekawati; Alizar Hasan; Feri Afrinaldi; Insannul Kamil; Rika Ampuh Hadiguna (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2026)
Cost of Quality (CoQ) is a critical tool in quality management, widely used to identify, evaluate, and optimize quality-related costs. While CoQ models such as the Prevention-Appraisal-Failure (PAF), Activity-Based Costing (ABC), Crosby, Opportunity Cost, and Process Costing have been extensively applied in discrete manufacturing systems, they remain underdeveloped for continuous production systems that exhibit time-dependent quality deterioration. This literature review explores the applicability of existing CoQ models to continuous and deteriorating systems. The analysis reveals that most CoQ models assume static failure behavior and do not accommodate gradual degradation or dynamic input quality. Among the models reviewed, the Opportunity Cost model is found to be the most conceptually aligned with dynamic loss due to declining quality, while ABC can complement it by tracing cost drivers linked to quality-related activities. Furthermore, this study outlines the potential of combining these models into a time-dependent dynamic CoQ framework, integrating deterioration functions and quality thresholds. Such a model could better represent the trade-off between prevention investments and the economic losses due to quality decay. Methodologically, this study employs a systematic literature review and comparative analysis to evaluate and synthesize prior CoQ models. The significance of this research lies in addressing theoretical and practical gaps in CoQ modeling for continuous production, which is increasingly important for industries striving for efficiency, competitiveness, and sustainability. This review ultimately provides a conceptual foundation for developing a mathematically optimized CoQ model for continuous systems, with potential validation through biogas production case studies